ON BENSTONITE AND BENSTONITE CARBONATITES - Sokolov S.V. (My University, 2001)
Sr-Ba-Ca-carbonates (which were initially identified as benstonite MgCa6Ba6(CO3)(13)) from carbonatite of the Murun, Aldan, and Jogipatti, Southern India, alkali massifs were studied by a complex of methods (X-ray diffraction, IR spectroscopy, thermal, and microprobe analyses). It is demonstrated that the high crystallization temperatures (840-610degreesC) and the complex multicomponent composition caused the postcrystallizational multistage decomposition of these carbonates. The exsolved phases predominantly have the benstonite structure but exhibit a disordered distribution of cations. Some of these phases can be referred to holo-type benstonite based on their chemistry, while others do not contain Mg and are most likely a high-temperature calcium analogue of benstonite. Benstonite proper is a relatively low-temperature mineral with an ordered distribution of cations (with magnesium occupying an "independent" position in the crystal structure). Because of this, it cannot be justifiable to consider the initial protocarbonates of the carbonatites to be benstonites. Since the structure of Sr-Ba-Ca-carbonates has not been determined, it is impossible to identify them as an individual mineral species, even if their chemical composition is known. The proportions of cations in the composition of the protocarbonates suggest that the carbonatites of the Murun and Jogipatti massifs should be attributed to the Sr-Ba-Ca type.